2022
DOI: 10.3390/metabo12100895
|View full text |Cite
|
Sign up to set email alerts
|

Histamine: A Mediator of Intestinal Disorders—A Review

Abstract: Within the gastrointestinal tract, histamine is present at relatively high concentrations, especially during inflammatory processes. Histamine is a biogenic amine with numerous effects on many cell types, mediated by the activation of its four different histamine receptors (H1–H4Rs). It is produced and released by immune cells as mast cells and basophils. Some cells such as dendritic cells or T cells can express histidine decarboxylase, an enzyme for histamine synthesis after stimulation. The same can be done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 122 publications
1
16
0
Order By: Relevance
“…Additionally, histamine is associated with various gastrointestinal disorders, such as irritable bowel syndrome ( Barbara et al, 2004 ) and inflammatory bowel diseases ( Dvornikova et al, 2023 ). Gut histamine can stimulates gastric acid secretion via H2R, induce abdominal discomfort through H4R activation ( De Palma et al, 2022 ), and enhance intestinal motility ( Mochizuki, 1953 ), leading to diarrhea ( Smolinska et al, 2022 ), a common clinical symptom in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, histamine is associated with various gastrointestinal disorders, such as irritable bowel syndrome ( Barbara et al, 2004 ) and inflammatory bowel diseases ( Dvornikova et al, 2023 ). Gut histamine can stimulates gastric acid secretion via H2R, induce abdominal discomfort through H4R activation ( De Palma et al, 2022 ), and enhance intestinal motility ( Mochizuki, 1953 ), leading to diarrhea ( Smolinska et al, 2022 ), a common clinical symptom in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…In Nile tilapia ( Oreochromis niloticus ), MFAP4 proteins are known to agglutinate and opsonize bacterial pathogens, which helps to prevent bacterial infections (88) . The histamine receptor 1, encoded by the hrh1 gene, is an effector of the action of histamine on phagocyte function in mammals and fish (89,90) . Overall, our results indicate that including yeast in the diet of rainbow trout could strengthen defense capacities of the gut, which is one of the main contact and entry points of pathogens and allergens in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also suggests that the number of mast cells may be increased in the stomach and duodenum in patients with chronic urticaria independent of the occurrence of GI symptoms [ 19 ]. Histamine can play a crucial role in the occurrence of GI symptoms in patients with urticaria as its significant effects on the GI tract have been well described [ 20 ]. In a study by Guida et al plasma histamine concentrations were found to be higher in chronic spontaneous urticaria patients which may explain the presence of histamine-mediated symptoms including increase in stomach acid production [ 21 ].…”
Section: Discussionmentioning
confidence: 99%